Perancangan Aplikasi Multimedia Interaktif di SMK Negeri 7 Padang - Helvi Junia Eliza; Rini Sefriani; Rahmatul Husna Arsyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the Validity, Practicality, and Effectiveness of Interactive Multimedia Applications in the Subject of Basic Dance Movement in Class X Students of the Dance Department at SMK N 7 Padang. This research and design was carried out with 38 class X students of the Department of Dance at SMK N 7 Padang. This type of research is R&D using the Four-D model. With the following steps. (1) define, (2) design, (3) development, and (4) disseminate. Overall the validity test assessment by the validator on application products is 89.87%, so that the validity level can be interpreted as Very Valid to use. The results of the practicality test assessment as a whole the practicality assessment of application products is 92.12%, so that the practicality level can be interpreted as Very Practical to use. The results of the effectiveness test obtained for application products amounted to 87.24% so that the level of effectiveness can be interpreted as very effective in use. It can be concluded that the Interactive Multimedia Application as a learning medium has been tested properly, is very practical and very effective to be used in the learning process in the subject of Basic Dance Movement class X, Department of Dance at SMK Negeri 7 Padang.